2015
DOI: 10.1177/0278364915608250
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional synthesis of three-fingered robot hands for maximal precision manipulation workspace

Abstract: This paper applies dimensional synthesis to explore the geometric design of dexterous three-fingered robotic hands for maximizing precision manipulation workspace, in which the hand stably moves an object with respect to the palm of the hand, with contacts only on the fingertips. We focus primarily on the tripod grasp, which is the most commonly used grasp for precision manipulation. We systematically explore the space of design parameters, with two main objectives: maximize the workspace of a fully actuated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Several studies have also demonstrated how underactuated hands can be leveraged to grasp and manipulate objects in unstructured environments and how this work may lead to adaptive hands that are relatively cheap, lightweight, and easy to control compared with fully actuated hands (43)(44)(45)(46)(47)(48). More recent work has optimized hand design to improve manipulation capabilities (49,50), providing open-source software for such design. Other recent work has suggested that the ability of compliant hands to deform in and with the environment may reduce the cognitive load of manipulation (51).…”
Section: Grasping: a Stepping Stonementioning
confidence: 99%
“…Several studies have also demonstrated how underactuated hands can be leveraged to grasp and manipulate objects in unstructured environments and how this work may lead to adaptive hands that are relatively cheap, lightweight, and easy to control compared with fully actuated hands (43)(44)(45)(46)(47)(48). More recent work has optimized hand design to improve manipulation capabilities (49,50), providing open-source software for such design. Other recent work has suggested that the ability of compliant hands to deform in and with the environment may reduce the cognitive load of manipulation (51).…”
Section: Grasping: a Stepping Stonementioning
confidence: 99%
“…This constraint shows that, see Figure 2, the motion of POM is fully constrained by the motion of grasp contacts, and can be uniquely described by the motion of any three contacts in P. Although it is not a concern for threefingered hands, for which the three contacts cannot be colinear to maintain grasp stability, depending on the kinematic structure and the hand mechanism designs, it is important to ensure that the chosen three contacts are never colinear in order to construct the grasp frame, especially for hands with more than three fingers. Even if it is difficult to derive a motion model for underactuated hands, with the constraint in (6), the motion of the hand-object system can be modeled as a parallel mechanism, for which the actuation inputs can be explicitly mapped to the object movements (Borràs and Dollar, 2015;Ma and Dollar, 2013).…”
Section: Hand-object Motion Modelmentioning
confidence: 99%
“…We believe we should extend the concept of generality to include not only grasping, but also the ability to perform as many manipulation tasks as possible in-hand. In this case, we need to consider an extra trade-off between in-hand manipulation ability and grasping generality [7].…”
Section: Related Work a Bimanual Manipulation Vs In-hand Manipumentioning
confidence: 99%
“…The rationale is that grasping involves symmetric movement where all fingers close around the object. However, such symmetry may not always be optimal for in-hand manipulation [7]. We introduce the idea that in one robotic hand some fingers can be devoted to grasping while others are responsible for performing manipulation actions, having completely different kinematic structures.…”
Section: B Grippers For In-hand Manipulationmentioning
confidence: 99%